Remoção de cromo e zinco por Aspergillus niger - Vale, Maria do Socorro (2010)
Microorganisms have been widely studied for the removal of various contaminants in wastewater, among them heavy metals. This study is the main approach of metal removal by filamentous fungus Aspergillus niger isolated from the effluent of a petrochemical industry. The research was divided into two parts, the first was to check the toxicity effect of Zn (II) and Cr (VI) by the fungus studied, since these pollutants can cause disturbances to microbial activity and eventually jeopardize the polluted environments and the second was the removal of these metals by biosorption using biomass in the form of pellets. The toxicity tests were done by testing the growth of the fungus, in semi-solid in the presence of different concentrations of metals. The adsorption tests were made with the pellets of live and dead biomass. The surface characteristics of biomass were evaluated by determining the point of zero charge, identification of sites of adsorption of biomass and analysis of scanning electron microscopy. To evaluate the adsorption capacity of biomass were performed kinetic studies and equilibrium adsorption. The toxicity studies indicated that the fungus has been studied more resistant to Zn (II) to Cr (VI), being completely inhibited at concentrations above 500 mg Zn (II).L-1 and 150 mg Cr (VI).L-1. The concentration of active ingredient capable of inhibiting 50% of mycelial growth is in the range and 100 to 150 mg.L-1 for the two metal ions. Biomass was observed in the presence of carboxyl groups, hydroxyl, amino and phosphate, indicating that this can be used for biosorption of metals. The fungus has fibrous structure, which favors the adsorption of metals. The adsorption of metals to the living biomass as the dead biomass, fitted kinetic models of pseudo-first order and pseudo second order and the equilibrium followed the Langmuir and Freundlich models for adsorbate concentrations smaller than 50mg.L-1 and the Freundlich model when adsorbate concentrations biggest than 50mg.L-1. This suggests the process of biosorption of metals occurs by physical and chemical mechanisms. Sorption capacities were found to 1,396 mg Zn(II).g-1 and 1,174 mg Cr(VI). g-1 for living biomass and 3,833 mg Zn(II).g-1 and 4,997 mg Cr(VI).g-1 for dead biomass. The dead biomass showed higher sorption capacity for removal of Cr (VI) as Zn (II). The fungus Aspergillus niger has a potential to remove Zn (II) and Cr (VI)